La promoción patronal de vivienda obrera en Camargo (Cantabria) a mediados del siglo xx - Cueto alonso, Gerardo J. (Ería, 2012)
RESUMEN El municipio de Camargo se convirtió en una de las principales áreas industriales de Cantabria a mediados del siglo xx. La necesidad de mano de obra generó a su vez la de viviendas que alojaran al creciente número de trabajadores. En algunas ocasiones, la promoción de vivienda obrera fue llevada a cabo por las propias empresas industriales. RÉSUMÉ La promotion patronale de logements ouvriers dans les années cinquante du xxe siècle à Camargo (Cantabrie, Espagne).- La municipalité de Camargo est devenue, vers la moitié du xxe siècle, une des principales zones industrielles de Cantabrie. De ce fait, le besoin de main-d’oeuvre a entrainé une demande croissante de logements pour les travailleurs. Dans certains cas, la promotion de logements ouvriers a été conduite par les entreprises industrielles elles-mêmes. ABSTRACT The employers’ development of workers’ housing in the fifties of the 20th century in Camargo (Cantabria).- The municipality of Camargo became one of the main industrial areas of Cantabria in the middle of the twentieth century. The requirements of workforce created, at the same time, the need of housing for the accommodation of the growing number of workers. In some cases the property development of workers’ housing was carried out by the industrial companies themselves. Palabras clave/Mots clé/Keywords Vivienda obrera, industrialización, promoción patronal, Cantabria, España. Logement ouvrier, industrialisation, promotion patronale, Cantabria, Espagne. Worker’s housing, industrialization, employer’s development, Cantabria, Spain.